Análise da compreensibilidade das demonstrações contábeis divulgadas pelo setor público brasileiro - Leite, Kalina Kely Miranda (2019)
Under the present situation of corruption scandals witnessed by the population and the increasing dissatisfaction with the performance of managers and the waste of public resources by the public administration, the citizens have increasingly demanded the responsibility of the government through demands for more transparency of the management acts of government agents. For this social control to be practiced, the quality of the information emitted in the financial reports should overcome the complexity of the terminology used by accounting. In this sense, the purpose of this research was to investigate the level of compressibility of the information disclosed by the accounting statements of the Brazilian public sector. More specifically, it was sought to verify if the knowledge of the technical language and the form of disclosure of this information influence the understanding of this accounting information, both for those who have knowledge of the technical language, and for the ordinary citizen without this knowledge. The methodology used was experimental research, using a control group (G1), which received no intentional stimulus and served as the standard for comparison, and three treatment groups (G2), (G3) and (G4), in which the manipulation of the independent variables, knowledge of the technical language and popular reporting, were performed to measure its effects on the comprehensibility of the accounting information of the public sector. For this purpose, students from higher education institutions and integrated high schools were randomly distributed in the experimental scenarios. The results of the research indicated that citizens who have the knowledge of technical language understand more the accounting information disclosed by the public sector than citizens who do not have this knowledge. In contrast, when the information was released through popular reports (popular reporting), the level of understanding was higher. Thus, it was concluded that the traditional way of presenting accounting information does not favor social control, due to its incomprehensibility, denoting that the popular reporting was better for this attempt.